NEW INTEGRAL INEQUALITIES PERTAINING CONVEX FUNCTIONS AND THEIR APPLICATIONS - Kashuri, Artion (Matematichki Bilten, 2021)
In this paper, first we prove a new generalized midpoint identity. By applying this identity some interesting midpoint type integral inequalities via \(s\)-convex functions are given. Some special cases obtained from our main results are discussed in details. Finally, some applications on the Bessel functions, special means of distinct positive real numbers and error estimation about midpoint quadrature formula are presented to support our theoretical results.